Health insurance status and severe mpox disease outcomes among sexual minority men in NYC: a retrospective cohort study - Ofole Mgbako; Cecilia Castellano; Kathryn Jano; Anthony Lo Piccolo; Madeline A. DiLorenzo; Dorothy Knutsen; Yusra Shah; Joyce C. Pressley; Dustin T. Duncan; Jason Felder; Dana Mazo (BMC Medicine)
Abstract Background The 2022–2023 global mpox outbreak predominantly affected sexual minority men, with notable racial/ethnic disparities in the USA. While the current literature has established the clinical predictors of severe mpox disease, little is known about the role of insurance status on clinical outcomes. We sought to characterize patients diagnosed with mpox in New York City (NYC) and examine associations between insurance status and mpox severity score (mpox-SS). Methods We included 143 patients aged 18 years and older between May 1, 2022, and December 31, 2023, with confirmed mpox identified through the electronic medical record. Demographics and clinical characteristics were summarized. Linear regression was performed to examine associations between insurance status and mpox-SS, controlling for race/ethnicity, high-risk condition (e.g., HIV with CD4 < 350 cells/mm3), prior vaccination with JYNNEOS or a smallpox vaccine, presence of a sexually transmitted infection (STI), and CDC Social Vulnerability Index. Results The mean age (SD) was 38.3 (10.2) years with 53 (37.1%) identifying as non-Hispanic White, 44 (30.8%) as Hispanic/Latino, and 30 (20.9%) as non-Hispanic Black. Over 90% were male sex at birth or identified as cisgender men and approximately 80% were sexual minority men. Ninety-six (67.1%) had private insurance, 6 (4.2%) Medicare, 35 (24.5%) Medicaid, and 4 were (2.8%) uninsured. Sixty-three (44.1%) had a confirmed HIV diagnosis, 25 (17.4%) patients had prior JYNNEOS vaccination, and 31 (21.7%) had a high-risk condition. Thirty-eight (26.6%) patients received tecovirimat; 21 (14.7%) patients were hospitalized, with 4 (2.8%) of those admitted to the ICU. The mean (SD) mpox-SS was 6.85 (3.36). In univariate analysis, lack of insurance or Medicaid status was associated significantly with more severe mpox-SS. Insurance status remained significant (p = 0.03) in multivariable models. Conclusions Being uninsured or on Medicaid was significantly associated with a higher mpox-SS in this diverse cohort of predominantly cisgender sexual minority men in NYC. High-risk status and lack of prior vaccination were associated with higher mpox-SS. Further studies are needed to assess the relationship between insurance, delays in access to care, or other socioeconomic inequities with severe mpox to understand the inequities beyond insurance access to prevent disparities in future outbreaks.